KONTRIBUSI KEPEMIMPINAN PEMBELAJARAN, MOTIVASI KERJA, DAN SARANA PRASARANA TERHADAP KEDISIPLINAN GURU DAN DAMPAKNYA TERHADAP KINERJA GURU SD DI KECAMATAN LAWEYAN SURAKARTA - Waluyo, Waluyo (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
The objectives of the research are to know and analyze the effect of instructional leadership, motivation, and school facilities on teachers’ discipline and their following effects on teachers’ performance both directly and indirectly of Elementary School Teachers of Laweyan Sub District of Surakarta. The type of the research is a survay research with correlational design. The population of the research were Elementary School teachers of Laweyan Sub District of Surakarta consist of 384 teachers. The sample of the research were 192 teachers selected using proportional random sampling. The data collection method was done using questionnaire. The technique of data analysis was done using path analysis of two paths.Based on the analysis, the research concludes that: 1) instructional leadership, motivation, and school’s facilities dicipline have a significant contribution on teachers’ performance indirectly through teachers’ dicipline both simultaneously and partially. It is indicated by the F statistic and t statistic results yielded; 2) instructional leadership, motivation, and school’s facilities have a significant contribution on teachers’ dicipline both simultaneously and partially. It is indicated by the F statistic and t statistic results yielded; and 3) teachers’ dicipline has significant contribution on teachers’ performance of elementary school teachers at Laweyan Sub District of Surakarta. It is demonstrated with the correlation coefficient yielded of 0.802 that significant at 0.000.